2022
DOI: 10.3390/nu14061195
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Respiratory Infections: Specific or Generalized Associations?

Abstract: Background: Based on our recently reported associations between specific dietary behaviors and the risk of COVID-19 infection in the UK Biobank (UKB) cohort, we further investigate whether these associations are specific to COVID-19 or extend to other respiratory infections. Methods: Pneumonia and influenza diagnoses were retrieved from hospital and death record data linked to the UKB. Baseline, self-reported (2006–2010) dietary behaviors included being breastfed as a baby and intakes of coffee, tea, oily fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 83 publications
(115 reference statements)
0
3
0
Order By: Relevance
“…Sufficient physical activity was considered to be ≥735 MET min/week [ 15 ]. A touchscreen food frequency questionnaire, which included the six main food groups, was created to create diet scores (theoretical range: zero to seven); those with a score greater than or equal to four were considered to have a healthy diet [ 15 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sufficient physical activity was considered to be ≥735 MET min/week [ 15 ]. A touchscreen food frequency questionnaire, which included the six main food groups, was created to create diet scores (theoretical range: zero to seven); those with a score greater than or equal to four were considered to have a healthy diet [ 15 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Either equal or more than 735 MET min/week was considered sufficient physical activity [14]. Diet scores (theoretical range: zero to seven) were constructed based on six main food groups from a touchscreen food frequency questionnaire, in which values greater than three were viewed as a healthy diet [14,20]. For each behavioural component, we assigned one point for a healthy level (zero points for an unhealthy level), then added up the points that ranged between zero and five, and classified the healthy behaviour index into three groups (no or one, two or three, and four or five).…”
Section: Assessment Of Healthy Behaviours and Other Covariatesmentioning
confidence: 99%
“…For instance, Vu et al discovered that in the UK Biobank (UKB) cohort, consuming coffee, tea, fish and fruit independently was associated with a decreased risk of future pneumonia or influenza events. On the other hand, consuming red meat was correlated with an increased risk ( 6 ) . Additionally, they also reported that higher consumption of coffee and vegetables, being breastfed and reducing intake of processed meat were associated with a reduced risk of COVID-19 infection ( 7 ) .…”
mentioning
confidence: 99%